A prospective examination of relationships between social media use and body dissatisfaction in a representative sample of adults. (March 2022) - Marques, Mathew D.; Paxton, Susan J.; McLean, Siân A.; Jarman, Hannah K.; Sibley, Chris G.
Highlights: Higher social media use significantly predicted body dissatisfaction one year later. Body dissatisfaction significantly predicted social media use one year later. Significant bidirectional relationships were present in women, but not men. These small effects were found in a large nationally representative adult sample. Implications for supporting broader community use of social media are discussed. Abstract: This study examined the temporal sequence of the relationship between social media use and body dissatisfaction in adults. A representative sample of adults (19–92 years old; M = 52.83, SD = 13.43; 62.02% women, 37.98% men) completed measures of social media use, body dissatisfaction, age, gender, BMI, and demographic variables in 2015, 2016, 2017, 2018 and 2019 ( N  = 6258) in the New Zealand Attitudes and Values Study. In the full sample, higher social media use was significantly associated with higher body dissatisfaction one year later, as was higher body dissatisfaction with higher social media use one year later after controlling for body dissatisfaction/social media use (T-1), gender, age, BMI, ethnicity, relationships status, and SES. Effects were small. The prospective pathway from social media use to body dissatisfaction was significant in all age groups but the reverse relationship was only significant in the middle aged and older groups. Both pathway directions were significant in women but only the pathway from body dissatisfaction to social media use was significant in men. The research has limitations and replication is required. However, findings suggest raising awareness about how to use social media positively across the broad community, not merely in adolescents, may be worthwhile.